Do Food Intake and Food Cravings Change during the Menstrual Cycle of Young Women? - Souza, Luciana Bronzi de; Martins, Karine Anusca; Cordeiro, Mariana Morais; Rodrigues, Ymárdila de Souza; Rafacho, Bruna Paola Murino; Bomfim, Rafael Aiello (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Objective The aim of the present study was to assess the anthropometric measures, food intake and food cravings during the menstrual cycle of undergraduate students of the faculty of nutrition.Methods A cross-sectional study was performed with 27 students from a public university in the state of Mato Grosso do Sul, Brazil, who had their food intake evaluated through a 24-hour food recall, their nutritional status evaluated based on anthropometric measures, and food cravings evaluated using the Food Desire Questionnaire. Data were collected during an evaluation in the follicular phase (between the 5th and the 9th day of the menstrual cycle) and another in the luteal phase (LP) (between the 20th and the 25th day of the menstrual cycle). For food intake variables, the analysis of variance (ANOVA) test was used, followed by the Tukey test. The Mann-Whitney test was used for the analysis of food cravings, considering a significance level of 5% (p < 0.05).Results The desire for foods rich in sugar, salt, and fat, such as chocolate, pastries, snacks and desserts were higher (p < 0.05) during the premenstrual period, although it did not reflect neither a higher energy intake nor an alteration in the distribution of macronutrients. A higher intake of carbohydrates, proteins, fibers, and calcium was observed during the LP; however, without statistical difference between the groups. There were no differences either in the intake of any food group or in the anthropometric measurements (p > 0.05).Conclusion Food cravings of nutrition students differed between the phases of the menstrual cycle; however, with no difference in food intake and in anthropometric measures.
Keywords: menstrual cycle; food intake; nutrition assessment; feeding behavior; luteal phase; follicular phase